Is wine perception influenced by sustainability information? Insights from a consumer experiment with fungus resistant grape and organic wines - Borrello, Massimiliano; Vecchio, Riccardo; Barisan, Luigino; Franceschi, Deborah; Pomarici, Eugenio; Galletto, Luigi (Food research international, 2024)
[Display omitted] •A within subject laboratory experiment was performed involving 162 wine consumers.•Sustainability information influence on perceptions of organic and FRG wines was measured.•Individual hedonic liking scores and willingness to pay (WTP) were collected.•Perception of organic (WTP + 13 %) is more impacted compared to FRG (WTP + 9 %). Literature has highlighted that the organic attribute has heuristic value for many consumers, representing an overarching signifier of positive characteristics. Nowadays a plethora of alternative systemic approaches side organic production in the aim to improve the overall sustainability of the agrifood sector. Current study, based on blind and informed tasting, measured sustainability information influence on respondents’ (n = 162) perceptions of organic and fungus-resistant grape (FRG) white wines. Findings of the within-subject non hypothetical experiment revealed that information has a stronger, positive impact on participants’ perception of organic wine (increasing 13 % monetary preferences) compared to FRG wine (+9%). Additionally, attitudinal characteristics driving consumers’ preferences towards FRG wine diverge from organic core motivations.